Spatiotemporal regulation of the GPCR activity of BAI3 by C1qL4 and Stabilin-2 controls myoblast fusion - Noumeira Hamoud (Nature Portfolio, 2018)
Myoblast fusion is an essential step in muscle growth and regeneration, and is regulated by the G-protein coupled receptor (GPCR) BAI3. Here Hamoud et al. show that the GPCR activity of BAI3 is spatiotemporally regulated during myoblast fusion, and identify C1qL4 and Stabilin-2 as, respectively, negative and positive regulators of its activity.